НАРНЫ ӨНДӨР ЦАЦРАГИЙН ЭРЧМИЙН ХОЛБОО - Б, Түвшинжаргал; Г, Даваахүү; Д, Батмөнх (Proceedings of the Mongolian Academy of Sciences, 2017)
In this work are brought some results of the measurement to intensities UV on territory of the Mongolia. Built curves to intensities UV depending on Sun, are evaluated UV in miscellaneous point territory.